2010
DOI: 10.7326/0003-4819-153-10-201011160-00006
|View full text |Cite
|
Sign up to set email alerts
|

Informing the Debate: Rates of Kidney Transplantation in Nations With Presumed Consent

Abstract: Canadian Institutes of Health Research and Lawson Health Research Institute.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 29 publications
1
61
0
Order By: Relevance
“…[9][10][11] Hospital factors associated with actual donation include large size, the availability of neurosurgical services, the presence of an emergency department and various unmeasured attributes. 2,27 The main limitations of previous studies were small sample, the use of self-report surveys or limited time spans. One previous study suggested that hospital identity might influence organ donation rates based on chart review at a subset of volunteer hospitals and was restricted to patients who were formally documented as having brain death.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Hospital factors associated with actual donation include large size, the availability of neurosurgical services, the presence of an emergency department and various unmeasured attributes. 2,27 The main limitations of previous studies were small sample, the use of self-report surveys or limited time spans. One previous study suggested that hospital identity might influence organ donation rates based on chart review at a subset of volunteer hospitals and was restricted to patients who were formally documented as having brain death.…”
Section: Discussionmentioning
confidence: 99%
“…These have included the effects on transplantation rates of religion 6,7 , probabilities of need 8 , demographic factors and attitudes 9 , marital status 10 , gender 11 , geographic variation 12 , presumed consent policies 13 and socioeconomic status 13 . While these studies have provided valuable insight into the potential for single locus variables to influence rates of renal transplantation, few have focused upon more than one country, and, while one 13 has focused on several of the variables included in our study, none has attempted to associate the relationships of so many different factors for both living and deceased KTR during a specific, homogeneous time frame, across such a large number of countries. Our univariate and multivariate analysis of 15 socioeconomic, policy and demographic factors across 54 different countries provides, to date, the largest and most comprehensive analysis of factors that may potentially influence KTR.…”
mentioning
confidence: 99%
“…A recent multinational study showed a higher rate of deceased donor kidney transplantation in 22 countries with presumed consent laws versus 22 other countries with explicit consent laws. 10 In this study, however, the only country from Asia with a presumed consent law was Singapore. Despite the implementation of an opt-out scheme including liver donation in revised legislation in 2004, there has been no increase in donor referral in Singapore 11 because it is legal but irrational and unethical to enforce deceased organ retrieval in the face of resistance from family members.…”
Section: Opportunities For Deceased Donation Legislationmentioning
confidence: 87%